Left atrial function index predicts poor outcomes in acute myocardial infarction patients treated with percutaneous coronary intervention - Tang, Yijin; Peng, Siling; Yao, Hui-ling; Liu, Zhibin; Zhang, Liang; Zhong, Changqing; She, Chang; Liu, Wei; Tang, Yi; Fu, Qinghua; Zhang, Yi (Frontiers in Cardiovascular Medicine, 2023)
Background and aims: The left atrial function index (LAFI) is an index that combines the left atrial emptying fraction, adjusted left atrial volume and stroke volume. The prognostic value of LAFI in acute myocardial infarction (AMI) patients treated with percutaneous coronary intervention (PCI) is unknown. This study aims to determine whether LAFI predicts prognosis in AMI patients treated with PCI. Methods: Patients with newly diagnosed AMI who were treated with PCI at Hunan Provincial People's Hospital from March 2020 to October 2021 were prospectively enrolled. All patients underwent transthoracic echocardiography (TTE) at baseline and follow-up. The endpoint events included rehospitalization due to unstable angina, nonfatal myocardial infarction, rehospitalization due to heart failure and cardiovascular death. Results: A total of 368 patients with AMI (92 women; mean age, 61.45 ± 11.91 years)were studied with a median follow-up of 14 ± 6.58 months. Sixty-nine patients had endpoint events. Patients who presented with events had a significantly lower LAFI than patients without events (34.25 ± 12.86 vs. 48.38 ± 19.42, P < 0.0001).Multivariate Cox analysis demonstrated that LAFI (HR = 0.97 [95% CI: 0.95;0.99]; P = 0.012) and the Killip classification (HR = 1.51 [95% CI: 1.03;2.22]; P = 0.034) were independently predictive of endpoint events. Kaplan-Meier survival curves showed that patients with LAFI ≤ 40.17 cm/ml/m 2 had higher events than patients with LAFI > 40.17 cm/ml/m 2 (HR = 8.53 [95% CI: 4.74;15.35]; P < 0.0001).LAFI is a strong and independent predictor of adverse events and can be used for risk stratification in patients with AMI treated with PCI.